2008
DOI: 10.1007/s11999-007-0064-8
|View full text |Cite
|
Sign up to set email alerts
|

Documentation of Associated Injuries Occurring With Radial Head Fracture

Abstract: We believe a better way is needed to accurately describe the spectrum of associated injuries that commonly occur in conjunction with a radial head fracture. A review of our institution's experience with 333 radial head fractures from 1997 to 2002 documented 88 (26%) associated injuries. Based on this clinical experience, our goal was to develop an accurate and comprehensive description of associated injuries. A shorthand suffix method first recognizes the type of radial head fracture with the traditional Mason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
1
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(71 citation statements)
references
References 35 publications
3
59
1
8
Order By: Relevance
“…Radial head fractures can occur in isolation or with associated elbow and forearm injuries, including fractures, fracturedislocations, and/or ligamentous injuries [9,11,32,35]. Options for treatment include nonoperative management [1,20], fragment or whole-head excision [6,15,21,24,30], open reduction and internal fixation (ORIF) [2,13,25,26,28], and radial head arthroplasty [7,8,10,14,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Radial head fractures can occur in isolation or with associated elbow and forearm injuries, including fractures, fracturedislocations, and/or ligamentous injuries [9,11,32,35]. Options for treatment include nonoperative management [1,20], fragment or whole-head excision [6,15,21,24,30], open reduction and internal fixation (ORIF) [2,13,25,26,28], and radial head arthroplasty [7,8,10,14,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Comminuted radial head fractures are complex elbow injuries. Of Mason type III radial head fractures, 75 % are associated with further ligamentous and osseous damage [7,12,23] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Excision can also be considered in patients with isolated, displaced comminuted radial head fractures that are not amenable to fixation [2] . Most comminuted radial head fractures, however, are not isolated [22] , and therefore excision alone is often contraindicated. Choosing to re-establish radio-capitellar mechanics [20] in Mason type 3 fractures by radial head arthroplasty or to preserve the radial head by internal fixation techniques remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…None of the studies identified in this systematic review gave this important baseline patient information. Recent studies have discussed the principles that guide decision-making in the management of comminuted radial head fractures [2,22,27] . Pike et al [2] recommended ORIF when feasible for all displaced (> 2 mm) radial head fractures consisting of less than four fragments.…”
Section: Discussionmentioning
confidence: 99%